S32 Cough suppression test: a novel objective test for chronic cough. (15th November 2017) - Cho, PSP; Fletcher, H; Turner, RD; Birring, SS
Abstract : Introduction: A recent functional MRI study has shown that patients with chronic refractory cough (CRC) have reduced activity in the areas of the brain associated with cough suppression. Cough challenge tests focus only on provoking cough and have limited clinical application due to the wide overlap between healthy subjects and patients with cough. We investigated whether patients with CRC could suppress cough in a cough challenge test. Methods: We recruited 13 chronic refractory cough patients and 11 healthy controls. Participants underwent an incremental capsaicin challenge test (0.49 to 1000 micromol.L -1 ) and were instructed "please do not cough during the test". The concentrations of capsaicin during the cough suppression (CS) protocol required to elicit 1 or more cough (CS1), 2 or more coughs (CS2), and 5 or more coughs (CS5) were documented. Patients with CRC also completed cough-severity and urge-to-cough visual analogue scales (VAS; 0–100 mm), and quality of life, Leicester Cough Questionnaire (LCQ; range 3–21). Results: Patients with CRC and controls had a mean (SD) age 57 (8) and 51 (7) years and 11 (85%) and 7 (64%) were female, respectively. CRC patients self-reported symptom and health status were; mean (SD) cough severity VAS 58 (31), urge-to-cough VAS 63 (30), and LCQ score 12.1 (4.4). Patients with CRC were less able to suppress cough compared to healthy controls; geometric mean (SD) CS1: 2.30 (3.56) vs 62.46 (5.62), CS2: 2.55 (3.71) vs 70.86 (5.91) and CS5: 3.37 (4.84) vs 321.70 (3.23) micromol.L -1 respectively, all p<0.0001. The mean difference (95% CI) in CS5 between CRC and controls was 6.6 (4.9, 8.3) doubling doses. CS5 was better than CS1 and CS2 at discriminating CRC patients from controls (figure 1 ). There was no significant association between CS5 and cough severity VAS (correlation coefficient, rs =0.29), urge to cough VAS (rs =0.24) and LCQ (rs =0.32), all p>0.10. Conclusion: Voluntary suppression of capsaicin-evoked cough is significantly diminished in chronic refractory cough. Our findings suggest future research should focus on cough inhibitory as well as activation pathways. CS5 has potential to be used as a diagnostic test and to evaluate anti-tussive therapy; this should be investigated further.